(untitled) (Revista Escenarios Sociojurídicos, 2025)
Environmental education emerges as a dynamic and continuous process that goes beyond the mere acquisition of knowledge, encompassing the awareness, values, and actions necessary to address current environmental challenges. In the university context, its importance lies in the formation of conscious citizens committed to environmental preservation. This presentation is the product of a project designed to promote an environmental culture at the University of Sinú, Cartagena Branch, focusing on solid waste management. It proposes an effective integration of environmental education with legal knowledge, leveraging existing legislation, such as Law 1259 of 2008 and Law 99 of 1993, to support and guide actions in favor of the environment. It is important to note that this article is the result of a research project that began in late 2024. Therefore, the conclusions presented at this time are provisional. The results will include progress made in the bibliographic review or the state of the art related to the research and presentation topic. Discussing the environment is essential, especially in a country like Colombia, where the human right to a risk-free, clean, healthy, and sustainable environment is recognized. This right is not only fundamental in itself but also crucial for the exercise of other rights, given its close connection with the right to life, respect for human dignity, and the conservation of nature and ecosystems (United Nations, 2022).